ABBREVIATION AS A MEANS OF SAVING LANGUAGE UNITS IN COMMUNICATION (Scientific journal of the Fergana State University, 2026)
This article explores the phenomenon of abbreviation as a key linguistic process and its role in achieving linguistic economy in communication. Based on the principle of language economy, abbreviations serve as efficient tools for conveying information concisely in modern discourse. The study analyzes the distinction between the terms “abbreviation” and “abbreviated form”, focusing on their psycholinguistic and pragmatic aspects, with practical examples from the legal domain. The findings emphasize the importance of abbreviations in optimizing communication by reducing speech time and cognitive load.